A mechanism for bistability in glycosylation - Mc Donald, Andrew; Tipton, Keith; Davey, Gavin (My University, 2018)
Glycosyltransferases are a class of enzymes that catalyse the posttranslational modification of proteins to produce a large number of glycoconjugate acceptors from a limited number of nucleotide-sugar donors. The products of one glycosyltransferase can be the substrates of several other enzymes, causing a combinatorial explosion in the number of possible glycan products. The kinetic behaviour of systems where multiple acceptor substrates compete for a single enzyme is presented, and the case in which high concentrations of an acceptor substrate are inhibitory as a result of abortive complex formation, is shown to result in non-Michaelian kinetics that can lead to bistability in an open system. A kinetic mechanism is proposed that is consistent with the available experimental evidence and provides a possible explanation for conflicting observations on the β-1,4-galactosyltransferases. Abrupt switching between steady states in networks of glycosyltransferase-catalysed reactions may account for the observed changes in glycosyl-epitopes in cancer cells.
Keywords: Glycosyltransferases; Enzymes; Kinetic mechanism; Glycan products; Cancer cells; Glycosyl epitopes; Cancer; Immunology, Inflammation & Infection; Neuroscience; BISTABILITY; Computational Biology; ENZYME KINETICS